ANALISIS FAKTOR EKSTERNAL DAN PERFORMANCE INDIKATOR BPRS INDONESIA TERHADAP PEMBIAYAAN SEKTOR PERDAGANGAN, HOTEL DAN RESTORAN - Achmad Adhi Wiyono; Sri Mulatsih (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2017)
The trade, hotels and restaurants sector is one of the economic sectors that have an important role in the growth of the national economy. However, the development of trade, hotels and restaurants are still not optimal, is evidenced by the continued decline in the proportion of financing in this sector. The main problem of the trade, hotels and restaurants in Indonesia is limited access to capital and the regulatory capital faced by the microfinance sector, so that the necessary role of the banking sector one of them through the BPRS. The purpose of this study to analyze performance indicators and external factors affecting BPRS financing for trade, hotels and restaurants in Indonesia. This study uses a model of Vector Error Correction with monthly data from January 2011 to July 2016. The results showed that the BI rate, inflation, PaR and DPK significant effect on the financing of trade, hotels and restaurants, whereas no significant effect Leverage. Keywords: BPRS, Financing, Performance, Trade hotel and restaurant.